Air Quality and Correlation of Exhaled Carbon Monoxide Level with Lung Function among Petrol Station Attendants in Banda Aceh - Hardisa, Rika; Kurniawan, Ferry Dwi; Dianova, Sri; Yanti, Budi; Yusuf, Nurrahmah (Respiratory Science, 2025)
Background: Risks of developing respiratory diseases due to pollutant exposures at petrol stations are high. The pollutants, such as particulate matter, carbon monoxide (CO), and volatile organic compounds emitted from vehicle exhaust and gasoline vapours, may affect the lung function of petrol station attendants. This study aimed to assess the levels of particulate matter, total volatile organic compounds, and the correlation of CO level and lung function among petrol station attendants in Banda Aceh. Method: An analytical observational study with a cross-sectional design involved 114 attendants from 12 petrol stations in Banda Aceh. Lung function was evaluated using spirometry, and CO exhalation levels were measured using a Smokerlyzer. In addition, particulate matter and total volatile organic compounds levels were measured in the petrol station area using an air quality monitor. Results: Most participants were male (82.5%) with a mean age of 30 years. The duration of work was under 5 years in 68 participants (59.6%). Approximately 61.4% (70 samples) were active smokers, with the most common Brinkman index indicating mild smoking habits for 50 samples (43.9%). The Pearson chi-square test revealed no significant relationship between CO exhalation levels and decreased lung function (P=0.118). The level of TVOC exceeded safe limits at all gas stations (>0.601 mg/m3), with an average TVOC level of 7.53 mg/m3. Most participants showed above-normal expiratory CO levels (53.6%). The average of the PM2.5 level was moderate. Conclusion: This study found no significant correlation between exhaled CO levels and decreased lung function among petrol station attendants, likely due to their shorter duration of work and age under 40 years.